2014
DOI: 10.1166/jbn.2014.1797
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Enhanced Electroporation for Mammalian Cell Transfection

Abstract: Electroporation figured prominently as an effective nonviral gene delivery approach for its balance on the transfection efficiency and cell viability, no restrictions of probe or cell type, and operation simplicity. The commercial electroporation systems have been widely adopted in the past two decades while still carry drawbacks associated with the high applied electric voltage, unsatisfied delivery efficiency, and/or low cell viability. By adding highly conductive gold nanoparticles (AuNPs) in electroporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…These NPs include DNAconjugated gold NPs with 100 to 200 nm diameter Kawano et al, 2006;Zu et al, 2014), silver NPs with 80 nm diameter (Lin et al, 2009), and hollow metal NPs coated with mesoporous silica layer with 65 nm diameter (Kim et al, 2011). These experimental studies demonstrated significant enhancement of delivery efficacy of NPs with the electroporation treatment.…”
Section: Physical Methods For Np Direct Deliverymentioning
confidence: 91%
See 4 more Smart Citations
“…These NPs include DNAconjugated gold NPs with 100 to 200 nm diameter Kawano et al, 2006;Zu et al, 2014), silver NPs with 80 nm diameter (Lin et al, 2009), and hollow metal NPs coated with mesoporous silica layer with 65 nm diameter (Kim et al, 2011). These experimental studies demonstrated significant enhancement of delivery efficacy of NPs with the electroporation treatment.…”
Section: Physical Methods For Np Direct Deliverymentioning
confidence: 91%
“…Meanwhile, an increase in cellular mortality can often be a great concern in these physical methods, if cells are subjected to the excess stress derived from the applied external forces. With regard to the direct delivery of NPs, the electroporation Kawano et al, 2006;Kim et al, 2011;Lin et al, 2009;Zu et al, 2014) and sonoporation (Carrasco et al, 2016;Wang et al, 2014;Yang et al, 2011) have been utilized in recent. In the following, these studies will be reviewed.…”
Section: Physical Methods For Np Direct Deliverymentioning
confidence: 99%
See 3 more Smart Citations